4t+5+4t-7t=6+2

Simple and best practice solution for 4t+5+4t-7t=6+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t+5+4t-7t=6+2 equation:


Simplifying
4t + 5 + 4t + -7t = 6 + 2

Reorder the terms:
5 + 4t + 4t + -7t = 6 + 2

Combine like terms: 4t + 4t = 8t
5 + 8t + -7t = 6 + 2

Combine like terms: 8t + -7t = 1t
5 + 1t = 6 + 2

Combine like terms: 6 + 2 = 8
5 + 1t = 8

Solving
5 + 1t = 8

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 1t = 8 + -5

Combine like terms: 5 + -5 = 0
0 + 1t = 8 + -5
1t = 8 + -5

Combine like terms: 8 + -5 = 3
1t = 3

Divide each side by '1'.
t = 3

Simplifying
t = 3

See similar equations:

| x^2(x^4+16)-8x=0 | | -5=5x^2-25x+25 | | log(6)(5x-3)=4 | | 25+2t=5(t+10) | | 8m+m=14+5m | | 7x+6x-4x=16+2 | | 2(m-3)=2(m-2.5) | | 30*50=x | | 30x*50=x | | 51-x=36 | | 14k(8-k+h)= | | 40c+120a=500 | | 5m-2=4+m | | -x-111+10x=33 | | -5x-6y-6x+7y= | | -5x-6y-6x+7= | | (7u^3-u^2-7)+(2u^3-4u^2)= | | 18x-8=-24 | | 0.80x=94 | | -3x^2+600x-3375=0 | | .50x+3+.80=1.80 | | 3b+1+b=2b+9 | | 3(y+2)=y+14 | | -9x-101-3x=79 | | 8x^2y+-5yx^2= | | 0.02x=5 | | x^2-200x+1125=0 | | (-a+5c)+(-7a+2c+3)= | | w+5.3=10.1 | | 25b+15= | | 7+(6x-5)4-30x= | | 9.2x-1.6x=28 |

Equations solver categories